Discovery of Genes Activated by the Mitochondrial Unfolded Protein Response (mtUPR) and Cognate Promoter Elements - Aldridge, Jonathan E. (Public Library of Science, 2007)
In an accompanying paper, we show that the mitochondrial Unfolded Protein Response or mtUPR is initiated by the activation of transcription of chop through an AP-1 element in the chop promoter. Further, we show that the c/ebpβ gene is similarly activated and CHOP and C/EBPβ subsequently hetero-dimerise to activate transcription of mtUPR responsive genes. Here, we report the discovery of six additional mtUPR responsive genes. We found that these genes encoding mitochondrial proteases YME1L1 and MPPβ, import component Tim17A and enzymes NDUFB2, endonuclease G and thioredoxin 2, all contain a CHOP element in their promoters. In contrast, genes encoding mitochondrial proteins Afg3L2, Paraplegin, Lon and SAM 50, which do not have a CHOP element, were not up-regulated. Conversely, genes with CHOP elements encoding cytosolic proteins were not induced by the accumulation of unfolded proteins in mitochondria. These results indicate that mtUPR responsive genes appear to share a requirement for a CHOP element, but that this is not sufficient for the regulation of the mtUPR. A more detailed analysis of promoters of mtUPR responsive genes revealed at least two additional highly conserved, putative regulatory sites either side of the CHOP element, one a motif of 12 bp which lies 14 bp upstream of the CHOP site and another 9 bp element, 2 bp downstream of the CHOP site. Both of these additional elements are conserved in the promoters of 9 of the ten mtUPR responsive genes we have identified so far, the exception being the Cpn60/10 bidirectional promoter. Mutation of each of these elements substantially reduced the mtUPR responsiveness of the promoters suggesting that these elements coordinately regulate mtUPR.